Perlindungan pada Citra Motif Kain Endek dengan Teknik Watermarking Menggunakan DCT Steganography - Dewa Agung Ayu Mutiara Dewi; I Gede Santi Astawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
This research develops a steganographic watermarking technique using the DCT method to protect the Endek fabric motifs. In DCT-based steganography method for watermark embedding in images, DCT transformation is used to separate the image into DCT coefficients that represent frequency information. The embedded watermark serves as an identification mark that is difficult to remove or modify without damaging the authenticity of the original motif. Accuracy testing using PSNR and MSE yielded average PSNR (54.367dB) and MSE (0.234), indicating that this technique is effective in preserving the authenticity and integrity of the Endek fabric motifs.